2023
DOI: 10.3390/ma16062322
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy on Designing Fluxes for Aluminum Alloy Melt Refinement

Abstract: With the aim of obtaining a refining flux that is stable and provides effective refining of aluminum melt, a new strategy of designing the flux composition has been proposed. Ten fluxes were designed, by selecting ten molten salt compounds according to their thermophysical parameters, physical properties, and thermodynamic analysis. The melting points of the ten fluxes, and the phases transformation of the fluxes after melting, were studied by DSC and XRD, respectively. The contact angles between four groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The existence of γ-Al2O3 indicates the presence of a thin oxide layer that enveloped the AlSi7Mg alloy during the in-situ casting process. Furthermore, Saleh et al [20] found that the observed phenomenon may be attributed to the elimination or detachment of the oxide layer present on the surface of the aluminium alloy chips. This occurrence results from the impact of the NaCl-KCl flux during the heating procedure, as seen under the specified conditions.…”
Section: Oxide Compounds and Phases Analysismentioning
confidence: 99%
“…The existence of γ-Al2O3 indicates the presence of a thin oxide layer that enveloped the AlSi7Mg alloy during the in-situ casting process. Furthermore, Saleh et al [20] found that the observed phenomenon may be attributed to the elimination or detachment of the oxide layer present on the surface of the aluminium alloy chips. This occurrence results from the impact of the NaCl-KCl flux during the heating procedure, as seen under the specified conditions.…”
Section: Oxide Compounds and Phases Analysismentioning
confidence: 99%
“…Their results showed the KF treatment effectively removed inclusion compared to the equimolar NaCl +KCl mixture, however, the addition of KF increased the porosity. Zhang et al [21] conducted a study on the effectiveness of different Na-based flux compositions on inclusion removal and porosity reduction in A6111 aluminum alloy and found that flux containing NaF showed the highest refining efficiency.…”
Section: Introductionmentioning
confidence: 99%